The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/jpm.2015.0089
|View full text |Cite
|
Sign up to set email alerts
|

The Language of End-of-Life Decision Making: A Simulation Study

Abstract: Background: Framing is known to influence decision making. Objective: The study objective was to describe language used by physicians when discussing treatment options with a critically and terminally ill elder. Methods: High-fidelity simulation was used, involving an elder with end-stage cancer and life-threatening hypoxia, followed by a debriefing interview. Subjects were hospitalist, emergency medicine, and critical care physicians from three academic medical centers. Measures were observation of encounters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Indeed, the language used to frame treatment options has been shown to influence treatment decisions. 25 This finding is also consistent with a prior study that found that a high-intensity medical center, compared with a lower intensity facility, was more likely to offer open-ended trials of life-sustaining treatments without addressing long-term goals. 26 Our study has several limitations.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the language used to frame treatment options has been shown to influence treatment decisions. 25 This finding is also consistent with a prior study that found that a high-intensity medical center, compared with a lower intensity facility, was more likely to offer open-ended trials of life-sustaining treatments without addressing long-term goals. 26 Our study has several limitations.…”
Section: Discussionsupporting
confidence: 89%
“…A third study included hospitalist, EM, and critical care physicians in a technologically advanced robotic simulation with a family member of a critically ill patient. Participants broached life-sustaining treatment differently than treatment focusing on comfort, commonly framing life-sustaining treatment as necessary while framing comfort measures as optional 42. These studies demonstrate that SBME allows researchers to investigate communication behaviors in a standardized setting that does not interfere with patient care.…”
Section: Discussionmentioning
confidence: 95%
“…SBME is a useful method to study and teach provider communication behaviors because it allows researchers to replicate particular clinical scenarios in ways not possible in real patient encounters. Several studies investigated the language used in discussions with patients, as well as how treatment options were framed 4042…”
Section: Discussionmentioning
confidence: 99%
“…Training in these competencies may improve nursing professionals’ attitudes toward end-of-life care [4], their levels of anxiety [5], and even the decision-making skills of patients and their families [6].…”
Section: Introductionmentioning
confidence: 99%